Biogenic synthesis of AgNPs using Artemisia oliveriana extract and their biological activities for an effective treatment of lung cancer. (12th November 2018) - Fard, Nafiseh Nafisi; Noorbazargan, Hassan; Mirzaie, Amir; Hedayati Ch, Mojtaba; Moghimiyan, Zeinab; Rahimi, Arian
Abstract: Silver nanoparticles (AgNPs) were synthesized using Artemisia oliveriana extract, and their physicochemical characteristics were studied. The antioxidant and antimicrobial activities of the AgNPs, as well as their anticancer effects on the lung cancer cell line (A549), using 1, 1-diphenyl-2-picrylhydrazyl (DPPH), MIC and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide (MTT) techniques respectively demonstrated that the synthesized AgNPs mainly affected the gram-positive bacteria rather than the gram-negative bacteria, and exhibited significant cellular toxicity on the A549 cell line. Further, the cellular uptake of the AgNPs results indicated that the AgNPs accumulated within the cell. Moreover, their impact on the expression of apoptotic genes including Bax, Bcl-2, caspase-3 (CASP3), caspase-9 (CASP9) and miR-192 using real-time PCR demonstrated substantial increase in the expression of all mentioned genes ( p <.001). Finally, the apoptotic effects of the AgNPs through DNA fragmentation test, flow cytometry and cell cycle analysis indicated the induction of apoptosis in the A549 cell line. The results revealed that the AgNPs synthesized using A. oliveriana extract have potential biological applications.